Structural color barcodes for biodiagnostics. Issue 2 (13th May 2020) - Shang, Luoran; Wang, Yuetong; Cai, Lijun; Shu, Yilai; Zhao, Yuanjin
Abstract: Suspension array technology has revolutionized the field of biodiagnostics due to its capability of multiplex assays. Construction of the barcodes is essential, where structural color barcode is one of the most satisfying candidates because of its stable encoding and convenient decoding features. Benefiting from microfluidics technique, structural color barcode particles have been synthesized with finely tuned size, configuration, and surface reactive moieties. This allows for the barcode's interactions with disease‐specific biomarkers at multiscale, from the molecular to the tissue/organ level. In this minireview, we present the very latest progress on structural color barcodes for biodiagnostic applications. We discuss in depth through typical examples of how the sensitive and efficient assays of different types of analytes are accomplished concerning the specific features entailed in the barcodes. We also provide critical thinking about the remaining challenges and future development of structural color barcodes from a biodiagnostics perspective. Abstract : Structural color barcodes with tailoring size, shape, structural, and bioactive moieties are finding extensive applications in the multiplex detection of disease‐specific biomarkers including at the molecular, subcellular, cellular, and organoids level, opening up new possibilities to the field of biodiagnostics.